Monkeypox vaccination in the global south: Fighting a war without a weapon - Isaac Olushola Ogunkola; Oyinloye Emmanuel Abiodun; Babatunde Ismail Bale; Emmanuel Ebuka Elebesunu; Somtochukwu Blessing Ujam; Innocent Chimaobi Umeh; Mfoniso Tom-James; Shuaibu Saidu Musa; Emery Manirambona; Salvador B. Evardone; Don Eliseo Lucero-Prisno, III (Elsevier, 2023)
Background: The Mpox outbreak awakened countries worldwide to renew efforts in epidemiological surveillance and vaccination of susceptible populations. In terms of Mpox vaccination, various challenges exist in the global south, which impede adequate vaccine coverage, especially in Africa. This paper reviewed the situation of Mpox vaccination in the global south and potential ameliorative approaches. Methods: A review of online literature from PubMed and Google Scholar concerning Mpox vaccination in countries belonging to the 'global south' category was done between August and September, 2022. The major focus areas included inequity in global vaccine distribution, challenges impeding vaccine coverage in the global south, and potential strategies for bridging the gap in vaccine equity. The papers that met the inclusion criteria were collated and narratively discussed. Results: Our analysis revealed that, while the high-income countries secured large supplies of the Mpox vaccines, the low- and middle-income countries were unable to independently access substantial quantities of the vaccine and had to rely on vaccine donations from high-income countries, as was the case during the COVID-19 pandemic. The challenges in the global south particularly revolved around inadequate vaccine production capacity due to lack of qualified personnel and specialized infrastructure for full vaccine development and manufacturing, limited cold chain equipment for vaccine distribution, and consistent vaccine hesitancy. Conclusion: To tackle the trend of vaccine inequity in the global south, African governments and international stakeholders must invest properly in adequate production and dissemination of Mpox vaccines in low- and middle-income countries.